2015
DOI: 10.1016/j.jevs.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Gymnastic Training and Dynamic Mobilization Exercises Improve Stride Quality and Increase Epaxial Muscle Size in Therapy Horses

Abstract: a b s t r a c tThe objective was to evaluate the efficacy of gymnastic training (GYM) and dynamic mobilization exercises (DMEs) on stride length (SL) and epaxial muscle size in therapy horses. Nine cross-bred hippotherapy horses that performed three, 25-minute therapeutic riding sessions per week throughout the study period were randomly assigned to three experimental groups: a control group in which the horses were sedentary with no additional physical activity; a group that performed DMEs; and a group that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 27 publications
3
34
0
7
Order By: Relevance
“…Evidence-based studies have shown that DMEs (baited stretches) increase the CSA of m multifidi. [20][21][22] The term dynamic indicates that the horse's musculature is actively moving the body, and mobilization implies that the joints are being moved through their full range of motion. However, the main benefit of these exercises lies in their ability to activate and strengthen the muscles that stabilize the spine rather than for enhancing flexibility.…”
Section: Principles Of Rehabilitation For the Core Musculaturementioning
confidence: 99%
See 4 more Smart Citations
“…Evidence-based studies have shown that DMEs (baited stretches) increase the CSA of m multifidi. [20][21][22] The term dynamic indicates that the horse's musculature is actively moving the body, and mobilization implies that the joints are being moved through their full range of motion. However, the main benefit of these exercises lies in their ability to activate and strengthen the muscles that stabilize the spine rather than for enhancing flexibility.…”
Section: Principles Of Rehabilitation For the Core Musculaturementioning
confidence: 99%
“…In the second study, 20 9 therapeutic riding horses were assigned to one of 3 groups, all of which continued their normal exercise regime throughout the study. This regime consisted of giving lessons of 25-minute duration 3 times per week on alternate days.…”
Section: Evidence-based Research On Dynamic Mobilization Exercisesmentioning
confidence: 99%
See 3 more Smart Citations